New vegetable variety from IIVR Kashi Haritima: a new Indian bean for better return - Rai, N; Lal, H; Yadav, DS; Rai, A B; Singh, P K (Indian Horticulture, 2019)
The Kashi Haritima is a pole type, medium-maturing and high-yielding (190-350 q/ha) Indian bean. On an average, it produces 3.4-4.2 kg pods/plant. The pods are 13.8-14.9 cm long, green, fleshy and free from parchment.